2013
DOI: 10.1097/eja.0b013e32835dcc45
|View full text |Cite
|
Sign up to set email alerts
|

Emotional sequelae among survivors of critical illness

Abstract: Adverse social and economic status is associated with higher rates of anxiety and depression following ICU stay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 32 publications
0
21
0
Order By: Relevance
“…For studies that reported potential risk factors, neither age nor gender were associated with anxiety in any study (0 of 5 (25,27,32,37,43) and 0 of 4 (22,27,37,43) studies, respectively). In addition, neither severity of illness, diagnosis at ICU admission, nor ICU/hospital length of stay were associated with anxiety (0 of 4 studies (25,32,35,37), 0 of 4 studies (27,29,35,37) and 0 of 4 studies (25,27,32,35), respectively).…”
Section: Resultsmentioning
confidence: 88%
See 3 more Smart Citations
“…For studies that reported potential risk factors, neither age nor gender were associated with anxiety in any study (0 of 5 (25,27,32,37,43) and 0 of 4 (22,27,37,43) studies, respectively). In addition, neither severity of illness, diagnosis at ICU admission, nor ICU/hospital length of stay were associated with anxiety (0 of 4 studies (25,32,35,37), 0 of 4 studies (27,29,35,37) and 0 of 4 studies (25,27,32,35), respectively).…”
Section: Resultsmentioning
confidence: 88%
“…Post-ICU depression and PTSD symptoms were strongly correlated with post-ICU anxiety symptoms (5 of 5 studies (21,25,35,37,38)). In addition, anxiety was associated with lower quality of life in 2 of 2 studies (23,25) (Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients discharged from intensive care unit (ICU) may experience psychological, cognitive, and physical dysfunction (Jones, ; Wolters et al ., ) resulting in a complex rehabilitation that extends well beyond hospital discharge (Kowalczyk et al ., ; Elliott et al ., ). Patients' relatives are also vulnerable to psychological pathologies and diminished health‐related quality of life (HRQoL) following the patients' critical illness (Wintermann et al, ).…”
Section: Introductionmentioning
confidence: 99%